2011
DOI: 10.1590/s1984-82502011000200012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fibrosis and vascularization of bone marrow stroma of chronic myeloid Leukemia patients treated with imatinib mesylate and their relationship with the cytogenetic response

Abstract: Chronic Myeloid Leukemia (CML) is a myeloproliferative disease characterized by the presence of the Philadelphia chromosome (translocation between chromosomes 9 and 22), resulting in the formation of the hybrid BCR-ABL protein. Currently, the treatment of CML patients is performed with imatinib mesylate (IM), which promotes the elimination of leukemic cells by inhibiting the kinase activity of BCR-ABL. This study evaluated the effectiveness of IM by monitoring 22 CML patients in a chronic phase treated at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In previous studies, our group demonstrated that IM acts to decrease the production of reticular fibers produced by stromal cells, suggesting a main activity in fibroblasts. Furthermore, we observed a correlation between fibrosis and vascularization of BM and cytogenetic response in patients with CML 37 .…”
Section: Discussionmentioning
confidence: 55%
“…In previous studies, our group demonstrated that IM acts to decrease the production of reticular fibers produced by stromal cells, suggesting a main activity in fibroblasts. Furthermore, we observed a correlation between fibrosis and vascularization of BM and cytogenetic response in patients with CML 37 .…”
Section: Discussionmentioning
confidence: 55%
“…There is a change in the distribution of elements in the extracellular matrix of the bone marrow and it has been suggested that the leukemia cells are protected or "hidden" by these elements. Some studies have shown that IM acts on bone marrow stroma ( 19 , 20 ) . The drug acts by blocking binding to the adenosine triphosphate (ATP), the binding site of the tyrosine kinase domain in the breakpoint cluster region/Abelson (BCR/ABL) protein and has also an independent anti-fibrotic effect in patients with CML.…”
Section: Discussionmentioning
confidence: 99%
“…The drug acts by blocking binding to the adenosine triphosphate (ATP), the binding site of the tyrosine kinase domain in the breakpoint cluster region/Abelson (BCR/ABL) protein and has also an independent anti-fibrotic effect in patients with CML. However, an increase of fibrosis could prevent the drug to act by not allowing apoptosis of Ph + cells ( 20 ) . A recent study demonstrated a significant correlation between cytogenetic response and the degree of reticulin thickening.…”
Section: Discussionmentioning
confidence: 99%
“…Besides increase in myeloid cells, the bone marrow microenvironment in CML is also altered. There is an increase in collagen type III (reticulin fibrosis) as well as an increase in angiogenesis [2]. Imatinib mesylate is a selective BCR-ABL protein tyrosine kinase inhibitor which acts by binding to the ATP binding site of BCR-ABL tyrosine kinase, causing its inactivation and thereby effecting apoptosis of leukemic cells which leads to improvement in bone marrow hematological and morphological parameters [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Imatinib also has effects on the bone marrow stroma and microenvironment. A decrease in bone marrow fibrosis has been observed in CML patients on imatinib therapy [2]. Recent studies have emphasized on the antiangiogenic property of imatinib.…”
Section: Introductionmentioning
confidence: 99%